1990
DOI: 10.1007/bf01244769
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a highly lipophilic Li+ lonophore in solvent polymeric membranes

Abstract: Ionophores based on non-cyclic triamides exhibiting Li § selectivity in solvent polymeric membranes are described. Their lipophilicity (water/1-noctanol partition coefficient) is up to 1013'8 so that they can be used in ionselective electrodes with a lifetime of up to 40 000 h even in permanent contact with whole blood or undiluted blood serum.Key words: ionophore for Li +, ion selective electrodes, high lipophilicity, solvent polymeric membranes.In view of the measurement of the lithium ion activity in whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Experimentally, we demonstrate the detection of primary and secondary ions based on IE and IT mechanisms by using single and double ionophores, respectively. Specifically, a thin poly­(vinyl chloride ) (PVC) membrane is doped with Na + -selective ionophore 1 or Li + -selective ionophore 2 (Figure ) to yield voltammetric responses not only to the primary ion, but also to the secondary alkaline earth ion based on the IE mechanism. The ratio of peak currents for the respective ions is assessed theoretically to confirm the formation of 1:1 complexes with both ions, which yields a net transferred charge, | z J |/ n J – | z I |/ n I , of +1.…”
mentioning
confidence: 99%
“…Experimentally, we demonstrate the detection of primary and secondary ions based on IE and IT mechanisms by using single and double ionophores, respectively. Specifically, a thin poly­(vinyl chloride ) (PVC) membrane is doped with Na + -selective ionophore 1 or Li + -selective ionophore 2 (Figure ) to yield voltammetric responses not only to the primary ion, but also to the secondary alkaline earth ion based on the IE mechanism. The ratio of peak currents for the respective ions is assessed theoretically to confirm the formation of 1:1 complexes with both ions, which yields a net transferred charge, | z J |/ n J – | z I |/ n I , of +1.…”
mentioning
confidence: 99%
“…We found that voltammetric selectivity was improved kinetically not only by rigid cyclic ionophores 1 and 2 with slow ion-binding kinetics , but also by flexible noncyclic ionophore 3 . These results suggest that the kinetics of facilitated ion transfer is not controlled by ion–ionophore complexation.…”
Section: Resultsmentioning
confidence: 77%
“…19 These results suggest that the kinetics of facilitated ion transfer is not controlled by ion–ionophore complexation. Specifically, thin-layer CVs of o NPOE/PVC membranes doped with ionophore 3 were nearly reversible for lithium ion (Figure 6A) and nearly irreversible for magnesium ion (Figure 6B) in separate solutions.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations